Targeting endothelial cells with golden spice curcumin: A promising therapy for cardiometabolic multimorbidity - Fei Tang; Dong Liu; Li Zhang; Li-Yue Xu; Jing-Nan Zhang; Xiao-Lan Zhao; Hui Ao; Cheng Peng (Pharmacological Research, 2023)
Cardiometabolic multimorbidity (CMM) is an increasingly significant global public health concern. It encompasses the coexistence of multiple cardiometabolic diseases, including hypertension, stroke, heart disease, atherosclerosis, and T2DM. A crucial component to the development of CMM is the disruption of endothelial homeostasis. Therefore, therapies targeting endothelial cells through multi-targeted and multi-pathway approaches hold promise for preventing and treatment of CMM. Curcumin, a widely used dietary supplement derived from the golden spice Carcuma longa, has demonstrated remarkable potential in treatment of CMM through its interaction with endothelial cells. Numerous studies have identified various molecular targets of curcumin (such as NF-κB/PI3K/AKT, MAPK/NF-κB/IL-1β, HO-1, NOs, VEGF, ICAM-1 and ROS). These findings highlight the efficacy of curcumin as a therapeutic agent against CMM through the regulation of endothelial function. It is worth noting that there is a close relationship between the progression of CMM and endothelial damage, characterized by oxidative stress, inflammation, abnormal NO bioavailability and cell adhesion. This paper provides a comprehensive review of curcumin, including its availability, pharmacokinetics, pharmaceutics, and therapeutic application in treatment of CMM, as well as the challenges and future prospects for its clinical translation. In summary, curcumin shows promise as a potential treatment option for CMM, particularly due to its ability to target endothelial cells. It represents a novel and natural lead compound that may offer significant therapeutic benefits in the management of CMM.